The red and the black : a chronicle of the nineteenth century - Stendhal, 1783-1842.; Robins, E. P.; Miller, Chris (Köln : Könemann, 2000)
A collection of critical essays on Stendhal's novel "The Red and the Black" arranged in chronological order of publication.
Keywords: Stendhal, -- 1783-1842. Rouge et le noir; Stendhal, -- 1783-1842. The red and the black; French fiction; Fransız romanı